Synthesis, Characterization and Applications of Gold and Silver Nanoparticles: From Antibacterial to Optoelectronic Nanomaterials - Djafari, Jamila (2019)
The Research and development of new metallic nanoparticles (NPs) have been booming in recent decades as a result of the advantageous properties presented by these nanomaterials. Their metallic nature associated with their tiny size induce physicochemical properties that constitute a real advantage for the construction of a new range of nano-metric materials with potential applications in biomedical, electronic, optical or catalytic fields, among many others. Until now, many scientific and technological fields are obtaining great benefits by the utilization and development of gold and silver nanomaterials. However currently, it is necessary to develop new reproducible methodologies allowing a greater understanding of the nano-scale materials thus promoting the construction of most precise and more complex gold and silver NPs through the control of their size, shape and composition, allowing new reviewed applications. With the aim to introduce new synthetic advances in the nanotechnology area, in the present doctoral thesis we have studied: i) The synthesis and characterization of bio-functionalized gold NPs with proteins; ii) The development of a nobel synthetic approach to produce gold and silver NPs using Tetracycline as synthetic agent; iii) The synthesis and functionalization of silver triangular nanoplates and their subsequent controlled organic and inorganic (silica layer) coating; and iv) the creation of a novelty synthesis of pseudo-spherical, multi-tip or raspberry like AuNPs using Iron (II) as Green reducing agent. Furthermore, the antimicrobial and optoelectronic properties of the produced NPs and their applications have been explored and studied.